Prevalence of claustrophobia and magnetic resonance imaging after coronary artery bypass graft surgery - Rita Katznelson (Dove Medical Press, 2008)
Rita Katznelson1, George N Djaiani2, Leonid Minkovich1, Ludwik Fedorko1, Jo Carroll3, Michael A Borger4, Robert J Cusimano5, Jacek Karski21Assistant Professor of Anesthesia; 2Associate Professor of Anesthesia; 3Registered Nurse, Department of Anesthesia and Pain Medicine; 4Associate Professor of Surgery; 5Assistant Professor of Surgery, Division of Cardiac Surgery, Toronto General Hospital, University Health Network, University of Toronto, Toronto, ON, CanadaBackground: The purpose of this study was to determine the prevalence of claustrophobia in patients undergoing magnetic resonance imaging (MRI) after coronary artery bypass graft (CABG) surgery.Methods: After IRB approval, we conducted a substudy of a prospective randomized controlled clinical trial of 311 patients evaluating administration of tranexamic acid and early saphenous vein graft patency with MRI after conventional CABG surgery. Chest tube drainage was measured at 6, 12, and 24 hours after surgery. The rate of transfusion and the amount of red blood cells (RBC), fresh frozen plasma (FFP), and platelets transfused were recorded.Results: A total of 237(76%) patients underwent MRI after surgery. 39 (14%, [95% CI, 10.2 to 18.0]) patients experienced severe anxiety caused by a fear of enclosed space in the MRI coil necessitating termination of the procedure. Patients with claustrophobia were on average 5 years younger. They were more likely to have diabetes mellitus and hypertension. Patients with claustrophobia had increased chest tube drainage during the postoperative period. The rate of blood product transfusion was similar between the two groups but patients with claustrophobia who were transfused received significantly more RBC and FFP than patients without claustrophobia.Conclusions: Postoperative claustrophobia and anxiety, leading to inability to undergo MRI, may be more common than previously described.Keywords: Claustrophobia, magnetic resonance imaging, cardiac surgery, bleeding